Centro de acolhimento para pessoas em situação de rua - Nascimento, Débora Ferro (Brasil, 2023)
According to the American psychologist Abraham Maslow, the basic physiological needs of human beings include access to clean water, food, exercise, rest and health (MASLOW, 2020). Homeless people, more specifically speaking, are those who most have their basic needs corrupted. The state of Amazonas is one of the Brazilian states with the highest number of people with income below R$ 497, from data from 2012 to 2021 - mainly in the city of Manaus, where the highest concentration of homeless people occurs in the central area of the city. With the aim of reflecting on this reality and making it more and more visible, the present work aims to develop an architectural project of a shelter/temporary reception center for people (adults and families) living on the streets in Manaus, so that their basic needs are met and they can also receive psychological support and other activities to reintegrate them into society.